# We start with the equation

Please check my work and give me the correct answer. Thank you.

We start with the equation:

X1^2-6*X1+2=0

X1(1)=1-6+2=(-3)

X1(2)+9-6*(-3)+2=29

X1(3)=29^2-6*29+2=841-174+2=669

X1(4)=669^2-6*669+2=443549

X1=1/3+1/29+1/669+1/443549=

.3333333+.0344828+.0014947+.00000023=.369311

This is approximately equal to .36454.

Thus A my answer

© BrainMass Inc. brainmass.com October 9, 2019, 5:46 pm ad1c9bdddfhttps://brainmass.com/computer-science/web-design/start-equation-67218

#### Solution Summary

The expert checks equations for the correct answers.

$2.19